(untitled) (Swiss Medical Weekly, 2013)
The immune system is able to specifically target antigen-expressing cancer cells. The promise of immunotherapy was to eliminate cancer cells without harming normal tissue and, therefore, with no or very few side effects. Immunotherapy approaches have, for several decades, been tested against several tumours, most often against malignant melanoma. However, although detectable immune responses have regularly been induced, the clinical outcome has often been disappointing. The development of molecular methods and an improved understanding of tumour immunosurveillance led to novel immunotherapy approaches in the last few years. First randomised phase III trials proved that immunotherapy can prolong survival of patients with metastatic melanoma or prostate cancer. The development in the field is very rapid and various molecules (mainly monoclonal antibodies) that activate the immune system are currently being tested in clinical trials and will possibly change our treatment of cancer. The ultimate goal of any cancer therapy and also immunotherapy is to cure cancer. However, this depends on the elimination of the disease originating cancer stem cells. Unfortunately, cancer stem cells seem resistant to most available treatment options. Recent developments in immunotherapy may allow targeting these cancer stem cells specifically in the future. In this review, we summarise the current state of immunotherapy in clinical routine and the expected developments in the near future.